Effect of the addition of carbon black and carbon nanotube to FeS2 cathode on the electrochemical performance of thermal battery - Choi, Yusong; Cho, Sungbaek; Lee, Young-Seak (Journal of industrial and engineering chemistry (Seoul, Korea), 2014)
Effect of the addition of conductive carbonaceous materials to the FeS2 (pyrite) cathode on electrochemical performance of thermal battery is investigated by adding carbon blacks (CBs) or multi-walled carbon nanotubes (MWCNTs) which has conductive network structures with various amounts from 0.1 to 1 wt.%, compared to the amount of pure FeS2. Among the samples prepared with various amounts of CB or MWCNT addition, the 1 wt.% CB-added sample exhibits the highest electrochemical properties. These results suggest that the improvement in the electrochemical performance of thermal batteries can be achieved by the addition of the conductive carbonaceous materials to pyrite electrode. KCI Citation Count: 40